2021
DOI: 10.3389/fphys.2021.697886
|View full text |Cite
|
Sign up to set email alerts
|

Approach Direction Prior to Landing Explains Patterns of Colour Learning in Bees

Abstract: Gaze direction is closely coupled with body movement in insects and other animals. If movement patterns interfere with the acquisition of visual information, insects can actively adjust them to seek relevant cues. Alternatively, where multiple visual cues are available, an insect’s movements may influence how it perceives a scene. We show that the way a foraging bumblebee approaches a floral pattern could determine what it learns about the pattern. When trained to vertical bicoloured patterns, bumblebees consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…We also aim to understand how flower patterns are learned and recalled through chromatic cues. Our previous findings in discrimination experiments hint at the possibility that bees do not always memorize every aspect of the pattern of a flower that they visit [18,19]. In the present study, we show that both chromatic and spatial pattern cues influence how bees choose between learned and novel patterns and colours in discrimination and recognition tests.…”
Section: Introductionsupporting
confidence: 61%
“…We also aim to understand how flower patterns are learned and recalled through chromatic cues. Our previous findings in discrimination experiments hint at the possibility that bees do not always memorize every aspect of the pattern of a flower that they visit [18,19]. In the present study, we show that both chromatic and spatial pattern cues influence how bees choose between learned and novel patterns and colours in discrimination and recognition tests.…”
Section: Introductionsupporting
confidence: 61%
“…As reviewed by Leonard and Masek [21], the results of multimodal experiments can be shaped by the salience of chosen stimuli. While existing literature supports that bumblebees can learn all of the stimulus values used in these experiments [31,32,39,40], our results indicate that in our FMPER experimental context, yellow and lily of the valley were more appetitive than their counterparts (blue and juniper berry) (figures 1,2). The FMPER experiments, while excellent for probing cognitive capability, are far from a free foraging environment; thus direct translation of this work into field preferences is premature.…”
Section: Not All Stimuli Are Created Equal: Color and Odor Values Inf...supporting
confidence: 41%
“…In addition, distance-dependent interaction effects show that final landing strategies may be controlled differently compared to approach flights. For bees, approaching flights from within 5–10 cm towards single- and two-colour blue/yellow stimuli are usually from below the target when the stimulus is arranged in the vertical plane 41 . Such a strategy in approach flights can lead insects to land in specific locations of the target, such as the LED lamp used here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for UV-A treatments we added red light for tracking purposes, which effectively increased the overall radiance of the stimulus, although the controls here showed that it had little or no influence on our main findings. On the other hand, colour contrast or a visual edge between two colours could aid thrips to differentiate visual cues more easily and induce them to land near boundaries of visual targets, as shown with other insects 41 , 44 . In our results, we found that for yellow and green, the landing sites were concentrated around the edge of the LED near the light contrast border between the LED and the black lamp frame.…”
Section: Discussionmentioning
confidence: 99%